Snow ecology : (Cambridge University Press, 2001)
The book opens up a new perspective on snow cover as a habitat for organisms under extreme environmental conditions and as a key factor in the ecology of much of the Earth's surface. Acknowledged experts in the disciplines that constitute snow science provide an understanding of the interrelationships between snow structure and life. The authors describe the fundamental physical and chemical processes that characterize the evolution of snow and the feedback mechanisms between snow cover and the life cycles of true snow organisms and biota of cold regions. The book also provides a study of the relationship between snow and climate and the paleoecological evidence for the influence of past snow regimes on plant communities.